2013
DOI: 10.1037/a0028894
|View full text |Cite
|
Sign up to set email alerts
|

The rate of source memory decline across the adult life span.

Abstract: Previous studies have suggested that the ability to remember contextual information related to specific episodic experiences declines with advancing age; however, the exact moment in the adult life span when this deficit begins is still controversial. Source memory for spatial information was tested in a life span sample of 1,500 adults between the ages of 21 and 80. Initially, images of common objects were randomly presented on one quadrant of a screen while the participants judged whether they were natural o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 54 publications
1
23
0
1
Order By: Relevance
“…such as an item was presented visually or auditorily during learningWilding, Doyle, & Rugg, 1995). Importantly for the present study, previous research suggests that source memory is substantially reduced in older adults (Anderson & Craik, 2000;Cansino et al, 2013;Spencer & Raz, 1995).…”
Section: Introductionsupporting
confidence: 52%
“…such as an item was presented visually or auditorily during learningWilding, Doyle, & Rugg, 1995). Importantly for the present study, previous research suggests that source memory is substantially reduced in older adults (Anderson & Craik, 2000;Cansino et al, 2013;Spencer & Raz, 1995).…”
Section: Introductionsupporting
confidence: 52%
“…Notably, sex separately interacted with each of these factors and with decade, indicating that it has an effect on working memory decline. This effect was shown to be completely absent in other types of memory, such as episodic memory (Cansino et al 2012). Although the comparison across decades revealed that the age at which significant declines in working memory occurred was dependent on the domain, the difficulty of the task, and the sex of the individual, the regression analyses demonstrated that discrimination declined across all of the adult life span, indicating that there is not a specific time point in adulthood when working memory starts to decline.…”
Section: Discussionmentioning
confidence: 95%
“…For men, discrimination decreased significantly in the third decade for the verbal and 2-back tasks, in the forth decade for the visuospatial tasks, and in the seventh decade for the 1-back tasks. Remarkably, the proportion of variance of working memory decline explained by age across the adult life span does not exceed 14 %; this proportion is half of that explained by age for other types of memory, such as episodic memory (Cansino et al 2012). This indicates that several other factors must be examined to further explain the changes that occur in working memory with advancing age.…”
Section: Reaction Timesmentioning
confidence: 94%
See 1 more Smart Citation
“…Podobnie, pogarszanie się pamięci epizodycznej, zależnej m.in. od hipokampa, w zakresie wydobywania kontekstowych detali wspomnień wydarzeń, również uznaje się za funkcję wieku (Cansino et al, 2013). Ponadto stwierdzono, że z wiekiem łagodnie pogarszają się funkcje pamięci topograficznej i chronologii oraz rozpoznawania wzrokowego (Gras et al, 2012).…”
unclassified